Ground reaction force of the hip, knee and ankle joints in adolescent idiopathic scoliosis: comparison between normal populations - Sivalingarajah, Prema (2016)
Background Scoliosis particularly Adolescent idiopathic scoliosis (AIS) is a relatively common condition seen in orthopaedic practice which can modify human locomotion. Thus far, no report yet on GRF comparison between pre- and post-operative treatment. This data is expected to give clinicians evidence based information on how scoliosis can affect all major weight bearing joints in term of its ground reaction force. Aim and Objective This study aimed to establish and compare the GRF on the three main weight-bearing lower limbs joints during a normal walking gait, among normal person, person with idiopathic scoliosis without spinal fusion, and person with idiopathic scoliosis with spinal fusion. Method Targeted subjects were recruited from Hospital Raja Perempuan Zainab II and Hospital Universiti Sains Malaysia, the two only referral hospitals for spinal cases in Kelantan, Malaysia. A total of 41 subjects fulfilling the recruiting criteria were recruited, namely control group without scoliosis (n=14), study group with scoliosis without spinal fusion (n=14), and study group with scoliosis with spinal fusion (n=13). The gait analysis was done at Sport Science Unit, School of Health Sciences, USM, equipped with an optical motion capture system consisting of six high-resolution digital cameras. These values were computed during walking on the gait platform over the force plate. Result GRF profiles for the three study groups on the three axes of the three weight bearing lower limbs joints versus walking phase was established. There was a noticeable trend observed in changing of X-axis and Z-axis GRFs versus walking phase on the three joints among the three study groups. The GRF was at baseline during the heel strike phase, and then it increased during the early stance and mid stance walking phases, the GRF decreased during the toe off phase and further decreased back to the baseline. Similar trend was also found in Y-axis GRF versus walking phase on the knee and ankle joints, but not the hip joint. In group comparison, there were no significant difference in the GRF of the three axes of the three joints between AIS without spinal fusion and normal groups. There were also no significant difference in the GRF of the three axes of the three joints between AIS with spinal fusion and normal groups. There were no significant difference in the GRF of the X and Z axes of the three joints between AIS without spinal fusion and AIS with spinal fusion groups. There was a significant difference was found between the AIS without spinal fusion group (44.00±26.78) and group of AIS with spinal fusion (17.85±17.21) at left knee Y-axis GRF, in which the GRF is significantly higher by mean difference of 26.15 in AIS without spinal fusion group. Conclusion Scoliosis had significant effect on the knee joints Y-axis GRF. Spinal fusion results in rebalancing of the knee joint Y-axis GRF, in which Y-axis force reflects the propulsive or braking force in a joint.